2019
DOI: 10.1016/j.cej.2018.09.136
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of electro-Fenton over electrocoagulation for disinfection of dairy wastewater

Abstract: This study is focused on the disinfection of raw dairy wastewater by means of a sequential treatment including an electrocoagulation (EC) step with an Fe|Fe cell followed by electro-Fenton (EF) or UVA-assisted photoelectro-Fenton (PEF). The two latter methods were run with an air-diffusion cathode for H2O2 generation and either a boron-doped diamond (BDD) or a RuO2-based anode. The inactivation of heterotrophic and lactic acid bacteria, Escherichia coli and enterococci was assessed. Low removal of organic load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“… 19 In particular, it was found that electrochemical treatment can result in the disinfection of dairy wastewater, along with the removal of organic loads. 20 …”
Section: Introductionmentioning
confidence: 99%
“… 19 In particular, it was found that electrochemical treatment can result in the disinfection of dairy wastewater, along with the removal of organic loads. 20 …”
Section: Introductionmentioning
confidence: 99%
“…M(OH) n ) which act as coagulant agents that catch and destabilize colloidal species in wastewater ( Çalışkan et al., 2020 ). Additionally, the H 2 gas bubbles generated at the cathode cause the flotation of pollutants and, consequently, an electro-flotation phenomenon can take place ( Bruguera-Casamada et al., 2019 ). With the integration of a UV energy source, photo-electrocoagulation processes emerge as an integrated approach in which the electro-dissolution of Fe or Al anodes is used to generate coagulant particles that not only remove suspended solids, colloidal material, pathogens as well as other dissolved solids in contaminated water (Eq.…”
Section: Indirect Oxidationmentioning
confidence: 99%
“…The EF process requires a short contact time, corroborating its economic justification. Moreover, there are further advantages, such as biocompatibility, versatility, controllability, and high decomposition rate of organic compounds, because of the continual regeneration of Fe 2+ on the surface of the cathode, which reduces the sludge production content in this process [15]. Despite its great potential window for purification of various kinds of wastewater, including alcoholic, shale gas, dairy, landfill leachate, textile industry, and pharmaceutical wastewaters [16], to date, this method has not been applied to treat effluents of soft drink wastewater.…”
Section: O2 + 2h + + 2e -→ H2o2mentioning
confidence: 99%